Uavnoma: A UAV-NOMA Network Model under Non-Ideal Conditions - Lima, Brena (2022)
Uavnoma is a set of Python functions and a front-end script for modeling, studying, and analyzing the communication system composed by an unmanned aerial vehicle (UAV) and two ground users. We assume that the UAV acts as an aerial base station to serve the users according to non-orthogonal multiple access (NOMA) principles. For more practical insights, residual hardware impairments (RHI) and imperfect successive interference cancellation (ipSIC) are considered. More specifically, uavnoma allows the modelers to study and visualize the system performance in terms of achievable rate and outage probability. Additionally, the package produces figures and tables showcasing results from the specified performance metrics. KEYWORDS: Non-orthogonal multiple access (NOMA); Non-ideal conditions; Numerical simulation; Performance analysis; Unmanned aerial vehicle (UAV)